From entrepreneurship education to entrepreneurial intention: Traversing the path of the dark, down, and destructive sides of entrepreneurship - Jeon, Haneul (Animo Repository, 2023)
Entrepreneurship education flourished as an essential ground in developing students’ creativity and innovative ways which can serve as panacea for social, economic, and environmental challenges. With the promising contributions of entrepreneurship, positivity bias must not be tolerated as there are unsuccessful entrepreneurial activities that have adverse impacts to the psychological (dark), capital (down), and societal (destructive) aspects. This study employed a mixed method approach in which data were collected through questionnaires and interviews by means of purposive sampling, garnering 122 survey responses and 10 interviewees. The statistical tools used to analyze the impact of entrepreneurship education (EE) on entrepreneurial intention (EI) through the mediators knowledge of the dark (DR), down (DW), destructive (DS) sides of entrepreneurship and strategies (STR) include simple and multiple linear regression analysis and partial least squares structural equation modeling (PLS-SEM) using Jamovi and SmartPLS 4. The results showed that DR, DS, and STR significantly mediate the relationship between EE and EI. Implications from the results emphasize the focus of educational institutions and government on increasing students’ awareness of the dark and destructive side of entrepreneurship and the strategies to reduce the sufferings generated in engaging in various entrepreneurial activities. Keywords: dark side of entrepreneurship, downside of entrepreneurship, destructive side of entrepreneurship